Entrepreneurial Transitions: Factors Influencing Founder Departure - Boeker, Warren; Karichalil, Rushi (Academy of Management Journal, 2002)
Research in entrepreneurship and life cycle theories of the firm have both suggested that new ventures may outgrow the managerial capabilities of their founding teams, at which point the founders may he replaced by professional managers. This study explored factors affecting founder departure. Results indicate that founder departure increases with firm size, decreases with founder ownership and hoard membership, and has a U-shaped relationship with firm growth. Founders who work in research and development or who are chief executives are also less likely to leave.